IMF Technical Assistance : Transferring Knowledge and Best Practice. (Pamphlet Series; Pamphlet Series, No., 2003)
An introductory guide to the IMF's technical assistance. Providing technical assistance to member countries-particularly developing countries and countries in transition-is at the core of the IMF's mission. Technical assistance, which includes training for government and central banks officials, is one of the benefits of IMFmembership. It complements and enhances the IMF's other key forms of assistance, id est, surveillance and lending. The IMF provides technical assistance mainly in its areas of expertise and responsibility: fiscal policy, monetary policy, and macroeconomic and financial statistics.